Respuesta :
Answer:
(x+6)(x-1)
Step-by-step explanation:
factor using the x-box method
Simplify:
Step-by-step explanation:
[tex]\ Given \ that:\\\\\ x^2 \ + 5\ x -6\\\\\ Solution: \\\\\ First \ calculate \ factor :\\\\\rightarrow \ x^2 \ + 5\ x -6\\\\\therefore \ first \ calculate \ factor \ that \ is \ 6 \ - 1\ = 5\\\\\rightarrow \ x^2 \ + (6-1)\ x -6\\\\\rightarrow \ x^2 \ + 6x-1x -6\\\\\rightarrow \ x(x + 6)-1(x+6)\\\\\rightarrow \ (x + 6) (x-1)\\\\[/tex]
Learn more:
- Simplify: https://brainly.in/question/13979352